GENERALISATION OF LEARNED LESSONS IN DESIGN OF FREIGYT CARS TRUCKS FOR THE CREATION OF THEIR STANDARD SERIES - Boronenko, Yu. P.; Orlova, O. M. (Science and Transport Progress, 2004)
The paper generalizes experience of the latest scientific and practical developments in the field of freight bogies that can be implemented in the type series. Bogie types are split into classes by design speed, and technical solutions for each type are provided. The series also contains three types of groups with different axle loads. Scientific and design problems that are still to be solved are formulated.